Семантичний рівень емотивності англомовного дискурсу. - Цинтар, Наталя (Актуальні питання гуманітарних наук: міжвузівський збірник наукових праць молодих вчених Дрогобицького державного педагогічного університету імені Івана Франка., 2020)
The article is devoted to the comparative analysis of the semantic representation of the emotivity in the literary works of the female authors in the XIX and XXI centuries. The semantic research of the emotivity was conducted according to the axiological differentiation of the emotions (positive, negative, ambivalent). The total selection of the lexical semantic representations of the category of emotivity contains 3 354 examples. It was stated that the negative emotivity is presented by 50 alothemes, positive emotivity – 26 alothemes and ambivalent emotivity is presented by 11 alothemes. It is was proved that according to the general amount of the contextual realization in the literary works of the female authors of XIX century the group of the positive emotions is the most representative, at the same time in the works of the female authors of the XIX century the group of the negative emotions is the most quantitative. The negative emotivity in the literary works of the female authors is the most representative and has 1 629 examples among which were found 39 alothemes in the texts of the XIX century and 49 alothemes in the XXI century. The followings alothemes of the negative emotivity have the densest contextual reproduction: anger (170), fear (130) and despair (75). It was noticed that such alothemes 90 Актуальнi питання гуманiтарних наук. Вип 29, том 4, 2020 Мовознавство. Лiтературознавство of the negative emotivity as depression, despicableness, disbelief, dismay, hesitation, hopelessness, humiliation, hysteria, panic, revulsion, suspicion are found only in the texts of the XXI century. The alotheme of the negative emotivity boredom has its lexical semantic recreation only in the works of the XIX century. 1 276 examples represent the positive emotivity in the literary works under investigation: 865 in the XIX century and 411 in the XXI century. The positive emotivity in the works of the female authors of the XIX century is realized by 25 alothemes whereas in the works of the XXI century – in 26 alothemes. It was discovered that such alothemes of the positive emotivity in the works of the female authors as pleasure (195), joy (191), happiness (146) have the biggest quantity of the representations. The least representative are the followings alothemes of the positive emotivity: desire, pity, patience, respect and romance. According to the amount of the lexical semantic examples ambivalent emotivity is the least representative and has 449 examples: 190 – XIX century and 259 – XXI century. The most representative alothemes of the ambivalent emotivity are excitement (118), surprise (93) and shock (56). The analysis of the three types of the emotivity confirms the fact that the emotive component as an axiological representator of the alotheme is first and foremost during the perception the code of the communicative act that reflects the cultural thinking experience both of the narrator, and the corresponding literary epoch.
Keywords: negative emotions, positive emotions, ambivalent emotions, lexical semantic representations, alothemes, communicative act.